A Rare Case of Blastic Plasmacytoid Dendritic Cell Neoplasm Occurred in Postchemotherapy of Breast Cancer - Tong, Jiankun; Aksenov, Sergei; Siegel, Beth M.; Wei, Lihong; Rodgers, William H. (Case Reports in Hematology, 2023)
Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare and highly aggressive hematologic malignancy that arises from plasmacytoid dendritic cells. BPDCN typically presents with skin lesions and may involve peripheral blood, bone marrow, lymph nodes, or extranodal sites. It usually arises de novo, and some BPDCN cases are associated with or develop into myeloid neoplasms. Here, we report a case of a 57-year-old female presenting with cervical lymphadenopathy and skin rashes during the COVID-19 pandemic in 2021 following multiple types of postmastectomy therapy for breast cancer. The patient was ultimately diagnosed with BPCDN by lymph node biopsy. To the best of our knowledge, this is the first case report of BPDCN occurring postchemotherapy of breast cancer.